2021
DOI: 10.3390/su132011332
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Multiple Applications of Basil Species and Cultivars and the Effects of Production Environmental Parameters on Yields and Secondary Metabolites in Hydroponic Systems

Abstract: Basil (Ocimum basilicum L.), including other species and cultivars, is an excellent source of nutritional compounds, the accumulation of which can be stimulated by exogenous factors (environmental and nutritional conditions). Although best practices are relatively established for mature basil plants, microgreens production requires further research to optimize quality and quantity. The study objectives are (i) to provide an overview of the many uses of basil, (ii) collate and present common hydroponic systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 81 publications
0
14
0
1
Order By: Relevance
“…57(8) AUGUST 2022 levels of oxygen in the water can reduce plant growth and development, as well as increase the likelihood of pathogens in hydroponic systems (Yan et al, 2012). However, according to Ruso et al (2021), basil can persist with dissolved oxygen levels as low as 4 mg•L À1 , with optimal levels at 6.5 mg•L À1 . In the present study, dissolved oxygen rates were well above the minimum requirements for basil, thus elevated water temperature provided more benefits than could be accounted for by increased oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…57(8) AUGUST 2022 levels of oxygen in the water can reduce plant growth and development, as well as increase the likelihood of pathogens in hydroponic systems (Yan et al, 2012). However, according to Ruso et al (2021), basil can persist with dissolved oxygen levels as low as 4 mg•L À1 , with optimal levels at 6.5 mg•L À1 . In the present study, dissolved oxygen rates were well above the minimum requirements for basil, thus elevated water temperature provided more benefits than could be accounted for by increased oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…Soffer et al [61] found that chrysanthemums (Chrysanthemum x morifolium L. 'Bright Golden Anne') and the weeping fig (Ficus benjamina L.) both grew faster in oxygensaturated water. According to Ruso et al [62], basil can persist with DO levels as low as 4 mg L −1 , with optimal levels at 6.5 mg L −1 . However, lettuce only needs a DO content of at least 1.6 mg L −1 [63].…”
Section: Effects Of Hydrogen Peroxide On Dissolved Oxygenmentioning
confidence: 99%
“…Microgreens are emerging functional foods of the 21st century [2] that are gaining interest for their sustained nutraceutical properties and are an optimistic prospect for expanding especially for the consumption of the population in large urban areas and in terms of food security. Production of microgreens using hydroponic systems must be planned and controlled with care for controlling environmental factors in order to increase quality parameters [3][4][5][6]. This is in comparison to more conventional production methods using soil, considering all the controllable factors in hydroponic systems that have been shown to influence the accumulation of bioactive substances [7,8], the harvest timeframe [9][10][11], and the quality of the finished product [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, there is a wide range of environmental impact factors and variation in their relationships to downstream microgreens outputs, which means that there is no single prescription that will guarantee perfect results [26]. The literature review has demonstrated that there are optimal ranges within which one can begin the task of designing effective prescriptions for successful microgreen production [3,21,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation